(x-8)*0.3=5.7 8x/7=12 3(7x+8x-13x)=114 6.5x-3.7-2.8=6.5 解方程

来源:学生作业帮助网 编辑:六六作业网 时间:2024/05/20 13:42:53
(x-8)*0.3=5.78x/7=123(7x+8x-13x)=1146.5x-3.7-2.8=6.5解方程(x-8)*0.3=5.78x/7=123(7x+8x-13x)=1146.5x-3.7-

(x-8)*0.3=5.7 8x/7=12 3(7x+8x-13x)=114 6.5x-3.7-2.8=6.5 解方程
(x-8)*0.3=5.7 8x/7=12 3(7x+8x-13x)=114 6.5x-3.7-2.8=6.5 解方程

(x-8)*0.3=5.7 8x/7=12 3(7x+8x-13x)=114 6.5x-3.7-2.8=6.5 解方程
(x-8)*0.3=5.7
X-8=19
X=27
8x/7=12
8X=84
X=21/2
X=10.5
3(7x+8x-13x)=114
2X=38
X=19
6.5x-3.7-2.8=6.5
6.5X=6.5+6.5
X=2